Consequences of a virtual encounter with George Pólya - Mason, John (Teaching Mathematics and Computer Science, 2022)
The consequences of a virtual encounter with George Pólya as a teacher are recorded. An instance of his influence on my mathematical thinking is recounted through work on one of the problems in one of his books. Subject Classification: 01A99, 11A05, 97-03, 97D50